Unveiling the therapeutic mechanisms of Saorilao-4 decoction in pulmonary fibrosis through metabolomics and transcriptomics - Liu, Jiali; Song, Xiaowen; Song, Xinni; Fu, Xinyue; Niu, Shufang; Chang, Hong; Shi, Songli; Yang, Meiqing; Zhao, Ruiqi; Wang, Peng; Qi, Jun; Bai, Wanfu (Frontiers in Nutrition, 2025)
Pulmonary fibrosis (PF) is a challenging and intricate lung ailment to treat. Saorilao-4 decoction (SRL) is a traditional Mongolian medicine remedy frequently utilized in the management of lung disorders. This study employed transcriptomics and metabolomics to explore the molecular mechanisms of SRL in the bleomycin-induced PF rat model. Additionally, histopathological analysis and the assessment of serum biochemical indices were utilized to investigate the potential mitigating effects of SRL on PF. Transcriptomics and metabolomics analyses indicate that SRL primarily modulates the adenosine monophosphate-activated protein kinase (AMPK) and peroxisome proliferator-activated receptors (PPAR) signaling pathways by regulating genes such as Scd, Fads2, Cpt1a, Lipe, Pfkfb3, and Hmgcs2. Thereby influencing biomarkers such as S-Adenosylmethioninamine (SAM), 16-hydroxyhexadecanoic acid, and proline, mitigating metabolic disorders in pathways such as arginine and proline metabolism, vitamin B6 metabolism, fatty acid degradation, and arachidonic acid metabolism. The present study reveals the regulation of unsaturated fatty acid-related metabolic pathways in vivo and elucidates the mechanism of action of SRL in ameliorating PF.